A numerical study of effects of the axial stress on unsteady liquid pipeline flows. (30th March 2004) - Watanabe, Masaji; Kono, Yukio; Suito, Hiroshi
Abstract : We study the effects of the axial component of the shear stress on unsteady pipeline flows. We show that the axial component of the shear stress should be introduced in the modeling of unsteady flows, and as a numerical model, we propose a one-dimensional momentum equation in which a term containing the second derivative of the velocity with respect to space is introduced. The momentum equation and the continuity equation are converted into a system suitable for the application of upstream difference approximations. Numerical results are presented, and their correspondence with experimental results is examined to see how our model captures phenomena observed experimentally.